Migración e identidad: familias hispanoamericanas en Porto Alegre (Brasil) (2005)
This article presents a study made with 11 immigrant latin-american families in Gran Porto Alegre (Brazil); its purpose was to take account of identitary processes trough these families personal, culture, racial ethnic and national dimensions. Semi-structured interviews were made, which were analyzed through the content analysis method, from a priori categories. The results showed that theses families live non-cultural processes of cultural integration, in which they maintain their origin country customs and they adapt to the country they now live. Only one of the interviewed families presents cultural assimilitation, characterized by the loss of its origin culture. Index terms: family, migration, non-culture, identity.